How children represent sustainable consumption through participatory action research and co‐design of visual narratives. (September 2016) - Donovan, Doreen
Abstract: Children have the capacity to adopt active roles as citizens and are crucial contributors to explorations of contemporary consumption practices and a sustainable future. Yet, children are generally not explicitly encouraged to actively participate in constructing sustainable consumption discourses. This paper investigates how sixty South Australian, urban, public primary school children aged eleven to thirteen, participated in Participatory Action Research (PAR) and co‐design of visual narratives, in collaboration with a communication designer to create fifteen visual narratives expressing their views about consumption and sustainability. The aims of this research are to (1) use PAR to co‐design visual narratives examining how children understand consumption and sustainability in relation to consumption; (2) encourage children's critical engagement with issues of sustainable consumption; (3) examine how children's views on consumption can inform the design of future design interventions about sustainable consumption for young audiences. The research questions are: How do children represent consumption and sustainability through visual narratives; how can children actively contribute to sustainable consumption discourses; what can be learnt from children to inform the future design of activist artefacts about consumption for young audiences.